Agronomical and Physiological Behavior of Spanish Hazelnut Selection “Negret-N9” Grafted on Non-suckering Rootstocks - Rovira, Mercè; Hermoso, J. Francisco; Rufat, Josep; Cristofori, Valerio; Silvestri, Cristian; Romero, Agustí (Frontiers in Plant Science, 2022)
“Negret” is the most widely planted hazelnut cultivar in Northeastern Spain, where it is highly appreciated by the local kernel marked for its favorable nut traits. Its main disadvantages are the high suckers emission, causing large maintenance costs every year, and its medium-to-low vigor and susceptibility to iron chlorosis. In 2000, a trial to select new vigorous and non-suckering rootstocks for hazelnut was established at IRTA Mas Bové (Spain). The “Negret N-9” selection was grafted onto four clonal rootstocks (“Dundee” and “Newberg” two selections of open-pollinated Corylus colurna seedlings, the low suckering cultivar “Tonda Bianca” and the local selection “IRTA MB-69”) and compared to the self-rooted “Negret N-9” as a control. The trial was designed as a randomized complete block with 10 replications and one tree per plot (10 trees per treatment). Plant vigor, suckers emission, yield, and nut and kernel traits have been evaluated over 10 years (2003–2012). During the 2006 to 2010 growing seasons, the qualitative traits of kernels, such as kernel skin color, oil content, and fatty acid profiles, were added to the characterization. Physiological data, such as steam water potential, stomatal conductance, and leaf chlorophyll content, were also evaluated during the 2015 growing season. The results showed that clonal rootstocks had a strong influence on vigor and yield of “Negret N-9.” The “Dundee,” “Newberg,” and “IRTA MB-69” rootstocks showed the highest vegetative growth and the lower suckers emission. The yield was highest in trees grafted on “Dundee” rootstock. In terms of the qualitative traits of kernel which are important to the hazelnut industry, rootstocks increased the oil stability and induced a brown light color in the kernel pellicle versus the brown dark color observed in nuts collected from self-rooted “Negret N-9.” The fatty acids profile was also influenced by the grafting combination. Finally, physiological traits indicated a higher overall performances for “Dundee” rootstock, which was generally found to be the best rootstock for “Negret N-9” in the experimental environment.